2018
DOI: 10.3389/fmicb.2018.01350
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Non-structural Protein 4A Blocks the RLR-MAVS Signaling

Abstract: Flaviviruses have evolved complex mechanisms to evade the mammalian host immune systems including the RIG-I (retinoic acid-inducible gene I) like receptor (RLR) signaling. Zika virus (ZIKV) is a re-emerging flavivirus that is associated with severe neonatal microcephaly and adult Guillain-Barre syndrome. However, the molecular mechanisms underlying ZIKV pathogenesis remain poorly defined. Here we report that ZIKV non-structural protein 4A (NS4A) impairs the RLR-mitochondrial antiviral-signaling protein (MAVS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 52 publications
7
97
0
Order By: Relevance
“…However, to date, knowledge about the immune evasion strategies of NNV is very limited. Increasing evidence has shown that viruses have evolved a wide variety of mechanisms to evade the host immune systems through interfering with the RLR signaling [3,24]. Several studies have exhibited the relationship between viral infection-induced miRNAs and RLRs signaling pathway, and demonstrated many miRNAs functioned as negative regulators of RLRs signaling pathway during viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, knowledge about the immune evasion strategies of NNV is very limited. Increasing evidence has shown that viruses have evolved a wide variety of mechanisms to evade the host immune systems through interfering with the RLR signaling [3,24]. Several studies have exhibited the relationship between viral infection-induced miRNAs and RLRs signaling pathway, and demonstrated many miRNAs functioned as negative regulators of RLRs signaling pathway during viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, some studies indicate that ZIKV is a weaker inducer of type I IFN, as it failed to activate a quick and robust innate immune response, especially compared with other RNA viruses or mimetic reagents, such as Sendai virus (SeV) or RNA synthetic analog polyinosinic:polycytidylic acid [poly(I:C)] (24). Recently, some progress has been made in understanding the immune escape mechanisms of ZIKV (25)(26)(27). Yet despite these findings, for ZIKV, virus proteins responsible for the immune escape and their molecular mechanisms are not fully elucidated.…”
mentioning
confidence: 99%
“…Since RAB1B positively regulated induction of IFN-β, we hypothesized that it would also be required for antiviral responses driven by IFN. Therefore, we tested if loss of RAB1B resulted in higher levels of viral infection during Zika virus (ZIKV) infection, a virus known to be susceptible to type I IFN (21). We treated Huh7 cells with either an siRNA to RAB1B or control, infected these cells with ZIKV (multiplicity of infection (MOI) 0.01), and then 48 hours later measured the production of infectious ZIKV particles in the supernatant using a focus-forming assay.…”
Section: Resultsmentioning
confidence: 99%